8z+12x-3z-2x=

Simple and best practice solution for 8z+12x-3z-2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z+12x-3z-2x= equation:


Simplifying
8z + 12x + -3z + -2x = 0

Reorder the terms:
12x + -2x + 8z + -3z = 0

Combine like terms: 12x + -2x = 10x
10x + 8z + -3z = 0

Combine like terms: 8z + -3z = 5z
10x + 5z = 0

Solving
10x + 5z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5z' to each side of the equation.
10x + 5z + -5z = 0 + -5z

Combine like terms: 5z + -5z = 0
10x + 0 = 0 + -5z
10x = 0 + -5z
Remove the zero:
10x = -5z

Divide each side by '10'.
x = -0.5z

Simplifying
x = -0.5z

See similar equations:

| 20x-5=5(4x-1) | | 4w+10=n | | 32-7=57 | | 10(2x-3)+15-10x= | | 6x+8=2x-20 | | 4/7x-6/5=-3/2 | | 56.25=8.75a+12.50 | | 10x+15x-5=5(5x+7) | | 2x+17=3x-14 | | Y=In(11x) | | (11)(2.5)= | | -1x+7+2= | | Y=i | | 8.75+12.50=56.25 | | 2+16x^3=0 | | 23x+66=23x+91 | | (8x+7)+(-9x+2)= | | 7y+8(y-8)=26 | | 4x+12x-1=4(4x+2) | | Y=450000+1.3x | | 60x-500=3(3x)+2(5) | | 2(8)-5=2(8)-c | | R+(-9)=15 | | 52*150= | | 25(2n-8)=-100 | | 2(7)-5=2(7)-c | | 2(6)-5=2(6)-c | | 40=9n+4 | | 8.2(2m-10)=6.7+5.2 | | 2(5)-5=2(5)-c | | 96-95=x | | 2(4)-5=2(4)-c |

Equations solver categories